Integrating edTPA into Physical Education Teacher Education: Teacher Educators’ Perceptions and Experiences in Preparing Teacher Candidates - Olsen, Edward B.; Wyant, James D.; Tsuda, Emi; Laughlin, Michael K.; Baxter, Deborah S. (Journal of Teaching in Physical Education, 2024)
Purpose: In the United States, 15 states maintain policies and 25 states represent some level of edTPA affiliation. This study investigated how the edTPA was integrated and aligned into different physical education teacher education (PETE) programs in New Jersey. It also sought to understand teacher educators’ perceptions and experiences in preparing teacher candidates for the edTPA. Methods: This study utilized three data sources: semistructured interviews (n = 4), one focus group interview (n = 1), and documents (n = 17). Data analysis reflected a conventional approach toward qualitative content analysis. Results: In analyzing the data, four themes were established: (a) benefits and drawbacks of edTPA in PETE, (b) goals and success of edTPA in PETE, (c) integrating edTPA into PETE—macro- and microperspectives, and (d) analytic insights into edTPA and future recommendations. Discussion/Conclusion: In states requiring the edTPA, early exposure, scaffolding, curriculum mapping, and a shared mission and vision are critical. In states not requiring the edTPA, programs may want to consider indicators of performance, such as artifacts, reports, elements of the edTPA, university-based assessments, or a portfolio. Regardless of the type of assessment, “a” performance-based assessment may help to determine teacher candidates’ ability to plan, instruct, assess, and reflect.
Keywords: dept.hms; faculty; peer-reviewed; performance-based assessments; preservice teachers

Fostering cultural competence: Exploring client perception in a health coaching intervention among college students - Oh, Seungbin; Benes, Sarah; Yan, Zi (Nursing & Health Sciences, 2024)
Health coaching could be an innovative approach to develop student coaches' cultural competence (CC) among future health professionals. The current mix-method study design explored the impact of an 8-week peer health coaching intervention among college students on CC, from both student health coaches (i.e., students majored in health sciences who completed health coaching training and acted as health coach) and student clients' perspective. Nine student coaches and 24 student clients participated in the study. The quantitative analysis showed an increase in the clients' perceived level of coaches' CC between the pre- and posttest. The qualitative analysis revealed three themes, including varying levels of awareness, respectful and culturally responsive coaching, and cultural connection. Implications and recommendations for educators and researchers are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/nhs.13077
Keywords: cultural competence; cultural humility; dept.hms; health coaching; mixed-method design; peer-reviewed

Spinal cord injury management policies in high school sports as reported by athletic administrators - Scarneo-Miller, Samantha E.; Swartz, Erik E.; Register-Mihalik, Johna K.; Coleman, Kelly A.; Emrich, Christina M.; DiStefano, Lindsay J. (Translational Journal of the American College of Sports Medicine, 2024)
Introduction/Purpose Athletic administrators (AA) in U.S. high schools are uniquely positioned to provide guidance and endorsement for the prevention and management of common sport-related catastrophic injuries, such as the development of a spinal cord injury management (SCIM) policy. The purpose of this project was to evaluate AA’s knowledge of comprehensive SCIM policies in U.S. high schools. Secondarily, we aimed to investigate the factors, facilitators, and barriers to the development and adoption of comprehensive policies. Methods An online questionnaire was distributed to 6423 AA working in U.S.-based high school athletics, with 366 included in the final data analysis. The questionnaire evaluated AA’s knowledge of comprehensive SCIM policies addressing components of adoption, documentation, and communication. The questionnaire was developed based on the 2002 “National Athletic Trainers’ Association Position Statement: Acute Management of the Cervical Spine-Injured Athlete.” The questionnaire also inquired about facilitators and barriers to developing and adopting comprehensive policies. Proportions were calculated for policy adoption, and independent-samples t-tests evaluated the influence of athletic training services on comprehensive SCIM policies. Results About half of AA (49.2%, n = 180/366) reported having all recommended components of a written SCIM policy. AA who had access to an athletic trainer (yes = 62.9%, no = 18.1%, unknown = 19%) were more likely to have a comprehensive SCIM policy compared with those without access (80.6% vs 19.4%, χ21 = 7.091, P = 0.008, prevalence ratio = 1.24, 95% confidence interval = 1.03–1.50). The most commonly reported facilitator (49.9%) was “having a medical professional at the school,” and the main barrier (30.2%) was “my school would need more information, resources, assistance, etc.” Conclusions The findings identify areas for improvement in supporting the health and safety of children in high school participating in interscholastic athletics. Future dissemination and implementation research should develop strategies tailored to individual school community and need to improve SCIM policy adoption and implementation.
Keywords: dept.hms